INTEGRATING MENTAL AND SPIRITUAL HEALTH: INSIGHTS FROM THE HADITH ON MENTAL ILLNESS - Isdianto, Andik; Al Indunissy, Nuruddin; Fitrianti, Novariza (Multidisciplinary Indonesian Center Journal (MICJO), 2025)
This research focuses on eight mental illnesses listed in the hadiths narrated by Imam al-Bukhari and their implications for modern mental health understanding and practice. Employing a literature review methodology, this study analyzes and discusses the relevance of these mental illnesses—distress, sorrow, weakness, laziness, miserliness, cowardice, being debt-burdened, and being overpowered by others—in the context of contemporary psychology. The findings suggest that Islamic concepts of mental illnesses can provide new insights into therapeutic and clinical approaches, offering a framework for the integration of mental and spiritual health. The conclusion of this research emphasizes that integrating Islamic values into clinical psychology practices not only enriches theoretical understanding but also enhances the effectiveness of mental health interventions. The study further recommends the development of therapeutic programs that incorporate Islamic teachings, to support more inclusive and culturally sensitive mental health therapy approaches.